Cleaning and Sanitizing the Kitchen: Using Inexpensive Household Food-Safe Products - Janet Buffer; Lydia Medeiros; Mary Schroeder; Patricia Kendall; Jeff LeJeune; John Sofos; Amy Simonne (EDIS)
Consumers can protect themselves by preventing the spread of germs by both cleaning and sanitizing surfaces where food is prepared. This 3-page fact sheet provides instructions for sanitizing with bleach, vinegar, or hydrogen peroxide; and how to purchase "green" sanitizing products. Written by Janet Buffer, Lydia Medeiros, Mary Schroeder, Patricia Kendall, Jeff LeJeune, and John Sofos; adapted by Amy Simonne for use in Florida with permission and published by the UF Department of Family, Youth and Community Sciences, February 2012.